Fuzzy controlled SVC for power system damping - Zalina Kamis; Mohd Ruddin Ab. Ghani; Muhammad Nizam Kamaruddin; Hairol Nizam Mohd Shah (Institute of Advanced Engineering and Science, 2020)
This paper presents the ability of the fuzzy logic-based stabilizer used to generate the supplementary voltage control signal of the SVC to improve the damping of the inter-area mode oscillation in the power system. The base system is symmetrical, consisting of two identical areas connected by a relatively weak tie line. The SVC is chosen to be installed at the tie line midpoint. The active power of the local line will be used as an input signal for the stabilizer. The additional signal is calculated using fuzzy membership function to determine the quantity of reactive power supplied absorbed by SVC. The system oscillation is indicated by a 3-phase-to-ground short circuit occurring at 0.2s of the simulation and subsequently clearing after 100ms. Simulation with the sample power system shows that when subjected to a disturbance, fuzzy logic-based SVC stabilizer provides good damping in inter-area mode oscillation for the system. The effectiveness of the stabilizer applied with and without PSS will also be investigated.